(untitled) (Balneo and PRM Research Journal, 2021)
Introduction. Knee osteoarthritis is considered to be a chronic disease that affects the joints by causing pain, joint stiffness and decreased functional capacity. Regular physical activity can keep and increase functional capacity, it can reduce pain by improving movement behavior. The disruption of the sedentary behavior of the elderly patients with knee osteoarthritis can lead to improved physical function and general health. The purpose of this paper is to point out the role of physical activity in the elderly people diagnosed with knee osteoarthritis during the COVID-19 pandemic. Material and method. A total of 155 patients diagnosed (clinical and imaging) with knee ostoarthritis, who were treated on an outpatient basis, from May to September 2020, were studied. The parameters assessed in the study were pain, joint stiffness, the ability to carry out daily activities, anxiety and quality of life. Results and discussion.The studied group of patients was homogeneous in terms of the weight by age group and gender. Higher values were recorded in the study group in the evaluation of patients based on scales, the results being statistically significant, with value for p<0.05, which means that the hypothesis was validated. Conclusions. Patients of the study group recorded improvementin of functional capacity, joint stability and static and dynamic balance, which allowed a faster reintegration into the family and society.